Protamine-Induced Thrombocytopenia and Leukopenia - Al-Mondhiry, Hamid; Pierce, Williams S; Basarab, Robert M (Thrombosis and Haemostasis, 1985)
Protamine has been reported to cause thrombocytopenia and granulocytopenia. In this article, we report studies examining the relative contribution of protamine and heparin in the pathogenesis of this phenomenon, the dose-effect relationship, and the possible mechanism of cell loss. Protamine alone infused into experimental animals causes mild, transient granulocytopenia and thrombocytopenia. The sequential administration of heparin and protamine results in a more severe cytopenia lasting 30 to over 60 min. Organ scanning with 111In-labeled platelets shows a striking though transient accumulation of radioactivity in the lungs following heparin-protamine infusion. Platelet survival, however, is not shortened. Incubation of 125I-labeled protamine with blood cells in the presence of heparin results in tight binding of the drug to platelets and granulocytes. These observations suggest that protamine and heparin form a complex that binds to blood cells. The sequestration of coated cells in the lungs results in transient granulocytopenia and thrombocytopenia.
Keywords: Protamine; Thrombocytopenia; Leukopenia